Model Penjadwalan Pemeliharaan Preventif Mesin-Mesin Produksi untuk Meminimasi Total Tardiness - Eri Wirdianto; Irfan Nugraha Putra Mukhti; Alexie Herryandie Bronto Adi; Milana Milana (Universitas Negeri Padang, 2020)
Preventive maintenance is considered as a method to avoid unexpected failure in production machines. Unfortunately, conducting such maintenance is limited by resources availability thus likely causes tardiness. This research aims to minimize total tardiness of preventive maintenance on production machines by developing a scheduling model. This scheduling model takes the availability of time and labor into account to get an optimal scheduling model that can minimize the tardiness. The model of preventive maintenance schedule is developed by using the Integer Linear Programming method. This method provides output in the form of preventive maintenance schedule through a purpose function which considers the specified constraints on the company. As the result, the developed model could propose a preventive maintenance schedule which reduces the total tardiness.